Analisis Kesulitan Siswa Dalam Menyelesaikan Soal Matematika Materi Perbandingan Ditinjau Dari Tingkat Kemampuan Siswa Kelas VII SMP Negeri 1 Maluk Tahun Pelajaran 2020/2021 - Nufus, Hairun; Prayitno, Sudi; Baidowi, Baidowi; Turmuzi, Muhammad (Indonesian Publication Center, 2021)
This study aims to determine the types of student’s difficulties in solving the mathematical problem material of comparison evaluated from the ability level of students class VII of SMPN 1 Maluk in academic year 2020/2021. The type of research is descriptive quantitative research. The population of this study was students of class VII SMPN 1 Maluk. In determining the sample, the proportionate stratified random sampling technique was used. The sample in this study were 20 students and were taken randomly. The data collection techniques used were test and interview. The results obtained from the research that for high ability students in question number 1 they have difficulty in calculating of 38.88%, difficulty in transferring knowledge of 16.66%, difficulty in mathematical language of 50%, and difficulty in visual perception of 16. ,66%. In question number 2, high ability students have difficulty in calculating of 55.12%, difficulty in transferring knowledge of 52.77%, difficulty in mathematical language of 33.33%, and difficulty in visual perception of 83.33%. For medium ability students in question number 1 they have difficulty in calculating of 59.52%, difficulty in transferring knowledge of 57.14%, difficulty in mathematical language of 71.42%, and difficulty in visual perception of 28.57%. In question number 2, students with medium ability have difficulty in calculating by 71.42%, difficulty in transferring knowledge of 71.42%, difficulty in mathematical language of 85.71%, and difficulty in visual perception of 100%. For students with low ability in question number 1 they have difficulty in calculating of 73.80%, difficulty in transferring knowledge of 85.71%, difficulty in mathematical language of 85.71%, and difficulty in visual perception of 100%. In question number 2, low ability students have difficulty in medium ability of 100%, difficulty in transferring knowledge of 100%, difficulty in mathematical language of 100%, and difficulty in visual perception of 100%.